Response of morpho-physiological traits to drought stress and screening of curly pepper (Capsicum annuum) genotypes for drought tolerance (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rosmaina, Ridho A, Zulfahmi. 2022. Response of morpho-physiological traits to drought stress and screening of curly pepper (Capsicum annuum) genotypes for drought tolerance. Biodiversitas 23: 5469-5480. Developing drought-tolerant genotypes are required to face drought condition that often occurs. The study aimed was to assess the growth, biomass, yield traits, and gas exchange of fifteen curly pepper (Capsicum annuum L.) genotypes under normal and drought-stress conditions and to determine the key traits as indicators for selecting and identifying the drought-tolerant curly pepper genotypes. Fifteen curly pepper genotypes were cultivated under normal and drought-stress conditions. Twenty-one morphological and physiological traits were recorded in the reproductive phase. The data obtained were subjected to analysis of variance, Principal Component Analysis (PCA), and UPGMA dendrogram cluster analysis. This study showed that drought stress conditions significantly reduced plant growth, biomass, yield characters, photosynthesis rate, stomatal conductance, transpiration rate, and mesophyll conductance compared to normal conditions. Based on PCA analysis, stomatal limitation, mesophyll and stomatal conductances, root length, photosynthesis rate, fruit weight per plant, chlorophyll b, number of fruit, and transpiration rate were established as indicators for screening drought tolerant genotypes. The UIN-70 and UIN-65 were highly drought-tolerant genotypes according to the MFVD index. UPGMA dendrogram displayed clustering of the curly pepper genotypes consistent with the genotype's cluster based on the MFVD index. This study's findings can be utilized to improve curly pepper's drought tolerance in the future.
Keywords: Capsicum annuum, drought tolerance, gas exchange, growth, memberships function value of drought tolerance